Optimal Learning Guidelines: Secondary Mathematics - Trinidad and Tobago. Ministry of Education, Division of Curriculum Planning and Development (Division of Curriculum Planning and Development, Ministry of Education, 2021)
During the pandemic, face-to-face school in Trinidad and Tobago was closed in March 2020. Although some teachers continued teaching via online media, this did not become standardised practice until September 2020. Therefore, students would have lost approximately twelve (12) weeks of teaching time in 2020. In September 2020, remote learning was the prescribed mode of schooling with teachers using a combination of online teaching and preparing printed packages. At this time some students did not have access to devices and/or internet so they may have lost some teaching time due to these issues. Other factors may also be associated with a loss of learning time. Factors Associated with Loss of Learning • Students confined to their homes may spend less time in learning than when at school physically • Students confined to their homes may be stressed and anxious and this may negatively affect their ability to concentrate on schoolwork • Lack of in-person contact may cause students to be less externally motivated to engage in learning • Switching to online learning may negatively affect students who have difficulty adapting to this new learning environment • Switching to remote learning may exacerbate existing educational inequalities due to lack of access to adequate resources, unsuitable • home environment and parental support • Isolation from friends and teachers may result in unequal distribution of behavioural and psychological problems
Keywords: learning guidelines; secondary school; mathematics; learning loss; COVID-19; pandemic; curriculum adaptation